2014
DOI: 10.3762/bjnano.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Quantum size effects in TiO2 thin films grown by atomic layer deposition

Abstract: SummaryWe study the atomic layer deposition of TiO2 by means of X-ray absorption spectroscopy. The Ti precursor, titanium isopropoxide, was used in combination with H2O on Si/SiO2 substrates that were heated at 200 °C. The low growth rate (0.15 Å/cycle) and the in situ characterization permitted to follow changes in the electronic structure of TiO2 in the sub-nanometer range, which are influenced by quantum size effects. The modified electronic properties may play an important role in charge carrier transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The energy resolution at the N K-edge is better than 0.2 eV. The effectiveness of such in-situ growth using SXAS has been amply demonstrated during the growth of Cr [66], TiO 2 [67], TiN [68] and very recently for Fe films on MgO [69].…”
Section: In-situ System At Sxas Beamlinementioning
confidence: 99%
“…The energy resolution at the N K-edge is better than 0.2 eV. The effectiveness of such in-situ growth using SXAS has been amply demonstrated during the growth of Cr [66], TiO 2 [67], TiN [68] and very recently for Fe films on MgO [69].…”
Section: In-situ System At Sxas Beamlinementioning
confidence: 99%
“…The energy resolution at the N K-edge is better than 0.2 eV. The effectiveness of such insitu growth using SXAS has been amply demonstrated during the growth of Cr [66], TiO 2 [67], TiN [68] and very recently for Fe films on MgO [69].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent work, the CsPbBr 3 QDs with tunable particle sizes (3–12 nm) (Figure b) were successfully prepared by simply adjusting the reaction temperature, and their size‐dependent CO 2 reduction performance was then explored. It was demonstrated that the absorption edges of CsPbBr 3 QDs could be red‐shifted in the visible light region with the increment of the particle size probably owing to the quantum size effects . That is to say, the optical absorption properties and bandgap structure of the prepared CsPbBr 3 QDs could be effectively regulated by the quantum size.…”
Section: Photoelectrochemical Applications Of Ihpqdsmentioning
confidence: 99%